Kesadaran Hukum Masyarakat: Tantangan Terhadap Penghapusan Kekerasan Dalam Rumah Tangga Di Kabupaten Pesawaran, Lampung - Rodliyah, Nunung; Andreas, Ricco; Murniati, Rilda; Mustika, Dora; Kulsum, Sayyidah Sekar Dwi (Al Huwiyah: Journal of Woman and Children Studies, 2024)
Violence against women and children is one of the criminal acts in Indonesia, one of which is domestic violence that often occurs in a marriage bond. The victims in this crime of domestic violence are usually women and children. The government has issued Law Number 23 of 2004 concerning the Elimination of Domestic Violence, but this is not enough to anticipate such violence. This can happen due to the low legal awareness of domestic violence in family members.. The purpose of this research is to increase the knowledge and understanding as well as legal awareness of the people of Pesawaran Regency regarding the elimination of domestic violence, especially regarding the content of Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Law Number 23 of 2002 concerning Child Protection, legal protection procedures for victims of domestic violence, and the fulfillment of the rights of victims of domestic violence in Pesawaran Regency and causes of domestic violence.. Education is not an incidental action but a continuous activity, Legal communication is the process of conveying legal messages in accordance with the content and a legal regulation with the aim of creating a common legal understanding or understanding. It is necessary to have non-formal education or legal communication aimed at community members, non-formal education or legal communication is carried out by means of Socialization and Counseling of Law No. 23 of 2004 concerning the Elimination of Domestic Violence.